Research On the Influence Mechanism of The Digital Capability ofChinese Manufacturing Enterprises on Organizational Resilience (Revista Galega de Economía)
The development of digital technology has brought great impact and changes to the management practice of Chinese manufacturing enterprises. Improving the digital ability of enterprises, so as to improve the internal and external environment adaptability of enterprises, and enhancing the resilience of enterprises is an urgent consideration for every enterprise. Based on the theory of Dynamic ability and Knowledge management, this paper discusses the internal action mechanism of digital ability (digital technology application ability and digital resource integration ability) on organizational resilience, and verifies the intermediary role of Ambidextrous innovation and the regulatory role of knowledge management. This paper uses a sample of 400 senior managers of Chinese manufacturing enterprises to conduct empirical research, and the results show that: number Positive relationship between digital resource integration and organizational resilience; digital capability positively affects Ambidextrous innovation; Ambidextrous innovation partially mediates digital capability and organizational resilience; and knowledge management mechanism positively regulates the relationship between digital capability and organizational resilience. This paper puts forward management suggestions from the perspective of improving enterprise digital capability and enhancing organizational resilience, which provides inspiration and reference for enterprises to deal with unexpected threats and respond to crisis changes.